Implementación de Beamforming para Bluetooth V5.1 en una Agrupación Lineal de Antenas Mediante Radio Definido Por Software - Toasa Arroba, Fabricio Alexander (2020)
Using a positioning system identifying the angle of arrival (AoA), and the intensity of the received signal, to determine the direction of the signal, as a method for forming beams towards specific recommendations is intended to increase the performance and efficiency of the radiated power, improve quality of service while minimizing interference from other directions. In the present investigation, the experimental evaluation of the arrival angle estimation and the implementation of Beamforming for the new Bluetooth Low Energy communication standard version 5.1 by Software Defined Radio in an antenna grouping synthesis. The system consists of a 4x1 uniform linear array, a radio frequency (RF) transceiver, and a baseband processor (BBP). Beamforming algorithms and AoA estimation are performed on digital data streams running on the baseband processor based on an FPGA. The proposed system, in addition to being low cost and affordable, can be adjusted for different antenna groups with a greater number of elements. The results obtained to determine the level of operability of the SDR platform to direct the main beam within a wide angular scanning range. This process is maintaining an excellent level of the main to secondary lobe, high rejection of interferences. At th e same time, the arrival angle presents a high level of precision while preserving a high power intensity in the received signal.